Save the children sponsorship management system - Musora, Farai (Midlands State University, 2019)
This project concentrates on developing the Save the Children Sponsorship Management system which was seen necessary after it was discovered that the command prompt system that was being used for sponsorship child records management had weaknesses. Poor communication through the use of multiple communication mediums led to difficulties in tracking the support tickets raised by users at Zimbabwe Power Company. The current system shows a lot of bureaucracy and old fashioned way of running systems. The fact that the field team has to create data files which are then send to CO for campaigning and send to IO takes time. This has caused a lot of queries from sponsors and IO when deliverables take time to reach them. Running two separate systems causes a lot of errors and child mismatch thereby raising queries on whether such children exist or not. The current system is also costly to the organization since it still requires the use of postage. A feasibility study was carried out to assess if the project was technically, economically and operationally feasible. It was then seen favorable to continue with the project since it was feasible. Information was gathered using interviews, questionnaires and observation to gather functional requirements of the system and problems faced by users with the old system. The design phase was conducted which included the system dataflow design, interface as well as database tables design. The Sponsorship Management System was developed using PHP, Bootstrap and HTML with SQL Server Database. The system developed was tested thoroughly using unit testing, sub system testing, acceptance testing, validation and verification. This was carried out to see that system was working without errors whilst the specifications and objectives of the system were met. The system conversion methodologies were evaluated and a parallel changeover was recommended to install the system as it gives users time to familiarize with the system. Also this means that anomalies can be rectified during this period. The organization will have backup from the old system so it can revert to the old system if the new system fails. Maintenance strategies were discussed and it was seen necessary to use them to ensure the continuity of the system, efficiency and effectiveness. Recommendations were made so that the system will make Save the Children a good environment for work through introducing a mobile application.